2016
DOI: 10.1016/j.virol.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The eIF4AIII RNA helicase is a critical determinant of human cytomegalovirus replication

Abstract: Human cytomegalovirus (HCMV) was recently shown to encode a large number of spliced mRNAs. While the nuclear export of unspliced viral transcripts has been extensively studied, the role of host mRNA export factors in HCMV mRNA trafficking remains poorly defined. We found that the eIF4AIII RNA helicase, a component of the exon junction complex, was necessary for efficient virus replication. Depletion of eIF4AIII limited viral DNA accumulation, export of viral mRNAs from the nucleus, and the production of progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…2k, human lung implant cells isolated from TB40/E-infected LoM were also Percolled. HCMV DNA levels in PB and tissue cells were measured by real-time PCR analysis as previously described 73 .…”
Section: Competing Interestsmentioning
confidence: 99%
“…2k, human lung implant cells isolated from TB40/E-infected LoM were also Percolled. HCMV DNA levels in PB and tissue cells were measured by real-time PCR analysis as previously described 73 .…”
Section: Competing Interestsmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol according to the manufacturer's directions as described previously (47,48). Briefly, cell pellets were resuspended in TRIzol and extracted with chloroform, and RNA was precipitated with isopropanol.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Polysomes and polysome-associated RNAs were isolated as described previously (47,48). Briefly, at the time of harvest, cells were incubated in normal growth medium containing 0.1 mg/ml cycloheximide (CHX) for 10 min.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The results demonstrated that eIF4AIII was a common target of three of the lncRNAs. The RNA helicase eIF4AIII plays important roles in human cytomegalovirus replication . Our results showed the potential influence of eIF4AIII on another herpesvirus, EBV, implying that EBV could probably modulate its own replication by dysregulating a few host lncRNAs.…”
Section: Discussionmentioning
confidence: 70%
“…The RNA helicase eIF4AIII plays important roles in human cytomegalovirus replication. [48][49][50] Our results showed the potential influence of eIF4AIII on another herpesvirus, EBV, implying that EBV could probably modulate its own replication by dysregulating a few host lncRNAs. The identification and elucidation of the mechanism of this interaction is underway in our continuing work.…”
Section: Target Genes Of the Ebv-related Lncrnasmentioning
confidence: 66%